2015
DOI: 10.1039/c5ee00250h
|View full text |Cite
|
Sign up to set email alerts
|

Positive onset potential and stability of Cu2O-based photocathodes in water splitting by atomic layer deposition of a Ga2O3buffer layer

Abstract: The improved energy band alignment of Pt/TiO2/Ga2O3/Cu2O structure results in a positive onset potential of ∼1 Vvs.RHE and a stable cathodic photocurrent under appropriate TiO2deposition temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
159
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 209 publications
(171 citation statements)
references
References 39 publications
1
159
1
1
Order By: Relevance
“…Indeed, Domen and co-workers reported recently an improved onset of photocurrent by judiciously replacing the Al:ZnO layer by Ga2O3 which displays a lower CB band offset with the Cu2O. 84 As shown in Figure 7b,c the ALD-deposited layers not only ameliorate the photocurrent response but also increase the lifetime from a few seconds to hours. 82 Similarly, Lee et al reported the improved stability of p-InP nanopillar photocathodes in acidic media upon coating with a layer (3-5 nm) of TiO2.…”
Section: Semiconductor Coatingmentioning
confidence: 94%
“…Indeed, Domen and co-workers reported recently an improved onset of photocurrent by judiciously replacing the Al:ZnO layer by Ga2O3 which displays a lower CB band offset with the Cu2O. 84 As shown in Figure 7b,c the ALD-deposited layers not only ameliorate the photocurrent response but also increase the lifetime from a few seconds to hours. 82 Similarly, Lee et al reported the improved stability of p-InP nanopillar photocathodes in acidic media upon coating with a layer (3-5 nm) of TiO2.…”
Section: Semiconductor Coatingmentioning
confidence: 94%
“…Gallium compounds12345 including gallium nitride (GaN), gallium oxide (Ga 2 O 3 ) and more recently gallium oxynitrides (GaON/Ga 3 O 3 N/Ga x O y N z ) have been known for their semiconducting and optoelectronic properties6789. These gallium materials in different morphologies have enlightened ample of applications e.g.…”
mentioning
confidence: 99%
“…In the case of the photoanode, self-oxidation makes it difficult to utilize non-oxide materials. In contrast, the photocathode can be made of a non-oxide material, such as p-type Si [16][17][18][19], copper oxide [20,21], phosphides [22][23][24][25], and oxysulfides [26,27]. Most photocathodes showing a relatively high half-cell solar-to-hydrogen conversion efficiency (HC-STH) [28] have been composed of single-crystalline materials, as in the cases of Si, InP, and InGaP2, owing to their low defect densities; however, these electrodes require time-consuming and costly processes to fabricate.…”
Section: Introductionmentioning
confidence: 99%